Dynamic characteristics and seismic response analysis of the bottle-shaped masonry ancient pagoda. (October 2022) - Wu, Xiaoqin; Lu, Junlong; Wang, Zhenshan; Yang, Wenjie; Qiao, Ningtian
Abstract: To study the dynamic performance and seismic response of the bottle-shaped masonry ancient pagoda of Mafo Temple, the numerical model of the pagoda was established using the finite element software ABAQUS with a hierarchical modeling method. By inputting the El-Centro wave, Taft wave, and Lanzhou artificial wave, the seismic response of the pagoda was calculated, and the seismic damage mechanism was analyzed, as well as the distribution characteristics of the principal tensile stress and the seismic weak area. The results show that the stiffness and mass distribution of the pagoda are consistent in the height direction, and the deformation of the Sumeru throne and the top of the pagoda is significant under the earthquake. The pagoda bottom exceeds the limits of the material's tensile damage factor and principal tensile stress under moderate and large earthquakes. The stiffness of the top of the pagoda is severely degraded under large earthquakes. Therefore, the Sumeru throne and the top of the pagoda are the seismic weak parts of the ancient masonry pagoda. These results provide a basis for the seismic capacity evaluation of the bottle-shaped masonry pagodas.